Capturing of particles in suspension flow through a micro cross-shaped channel. (May 2022) - Zhang, Wei; Wang, Yuan-ding; Li, Wei-feng; Liu, Hai-feng; Wang, Fu-chen
Highlights: The diluted suspension flow through a micro cross-shaped channel is studied. A range of particle capture modes in the cross-shaped channel are identified. The motion behaviors of isolated particles and their equilibrium orbits are analyzed. Abstract: Capturing of microscale particles through microfluidics has been a flourishing research area in chemical and biological engineering applications. This work follows our previous report (Zhang et al., AIChE J., vol. 66, 2019, e16822) by using micro plane laser-induced fluorescence (μPLIF) and high-speed photography technology to study the flow of a diluted suspension of buoyant particles in a micro cross-shaped channel at 30≤ Re ≤350. Particular attention is paid to particle accumulation behaviors caused by vortex breakdown within the steady engulfment flow and vortex shedding flow. Three particle capture modes are identified in accumulation regions including the particle chain mode, the steady and unsteady particle cluster mode at 100≤ Re ≤300. Multiple stable equilibrium orbits formed by captured particles in accumulation regions are attributed to the axial force balance. In addition, perturbations in particle trajectories induced by the vortex shedding flow or particle-particle interactions contribute to the particle release.